Solar radiation transfer for an ice-covered lake in the central Asian arid climate zone. Issue 1 (2nd January 2021) - Cao, Xiaowei; Lu, Peng; Leppäranta, Matti; Arvola, Lauri; Huotari, Jussi; Shi, Xiaohong; Li, Guoyu; Li, Zhijun
ABSTRACT: Spectral albedo and light transmittance through snow, ice, and water were measured in Lake Wuliangsuhai (40°36′–41°30′N, 108°43′–108°70′E), Inner Mongolia, China, during winter 2016. Data on the weather, structure of lake ice, and geochemistry of water were also collected during the 60-day field program. The study lake is shallow (mean depth 1.0–1.5 m) with a large wetland area. Compared with polar lakes, solar elevation is higher, snow accumulation is much lower, and the ice has more sediment. The ice was all congelation ice with a mean thickness of 36.6 cm, corresponding to a mean air temperature of −9.6 °C. The mean daily broadband albedo and photosynthetically active radiation (PAR) band transmittance were 0.54 and 0.08 (bare ice), 0.74 and 0.04 (new snow), and 0.30 and 0.12 (melting period), respectively. The level of light allowed photosynthesis to occur to the bottom of the lake. The ice acted as a grey filter for the sunlight with a mean attenuation coefficient of 2.1 m −1 . These results expand our knowledge of the evolution of light transfer through ice and snow cover and its role in the ecology of lakes in temperate and arid areas.